2002
DOI: 10.1104/pp.010585
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Characterization of a Mutation That Confers a Decreased Raffinosaccharide and Phytic Acid Phenotype on Soybean Seeds

Abstract: A single, recessive mutation in soybean (Glycine max L. Merr.), which confers a seed phenotype of increased inorganic phosphate, decreased phytic acid, and a decrease in total raffinosaccharides, has been previously disclosed (S.A. Sebastian, P.S. Kerr, R.W. Pearlstein, W.D. Hitz [2000] Soy in Animal Nutrition, pp 56-74). The genetic lesion causing the multiple changes in seed phenotype is a single base change in the third base of the codon for what is amino acid residue 396 of the mature peptide encoding a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
267
4
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(290 citation statements)
references
References 22 publications
12
267
4
4
Order By: Relevance
“…Hitz et al (2002) reported about the biochemical and molecular characterisation of a mutation that confers a decreased raffinose oligosaccharide and InsP6 phenotype on soybean seeds. This can be explained by the fact that InsP6 and raffinose oligosaccharides share at least myoinositol-1-phosphate and possibly free myo-inositol as a common intermediate (Loewes and Murthy 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hitz et al (2002) reported about the biochemical and molecular characterisation of a mutation that confers a decreased raffinose oligosaccharide and InsP6 phenotype on soybean seeds. This can be explained by the fact that InsP6 and raffinose oligosaccharides share at least myoinositol-1-phosphate and possibly free myo-inositol as a common intermediate (Loewes and Murthy 2000).…”
Section: Discussionmentioning
confidence: 98%
“…However, relatively little is known about plant genomic sequences encoding functions in the late part of the pathway, playing a direct role in seed InsP6 accumulation and mobilisation (Raboy 2001). Only recently, Hitz et al (2002) reported that a defective myoinositol-1-phosphate synthase decreased the amount of InsP6 in soybean seeds. Furthermore, it is known that during germination InsP6 is broken down by phytase enzymes, releasing myo-inositol and mineral contents.…”
Section: Introductionmentioning
confidence: 97%
“…Inositol can be converted into phytic acid (phytate), the most abundant form of phosphate in seeds, accounting for 50-90% of total seed phosphorus in several species (Loewus and Murthy 2000;Raboy 2001Raboy , 2002Raboy et al 2001). The path to phytate has been suggested to proceed via the sequential phosphorylation of inositol phosphates, and/or in part via phosphatidylinositol phosphate (Brearley and Hanke 1996a, b;Loewus and Murthy 2000;Raboy 2001Raboy , 2002Hitz et al 2002). Phytate is presumed to act as a phosphate storage compound (Brearley and Hanke 1996a, b).…”
Section: Introductionmentioning
confidence: 97%
“…Jones et al (1999) screened 70 pea lines from the John Innes Pisum germplasm collection (Norwich, UK) and selected lines which had unusual RFO composition: traces of raffinose or verbascose and a broad range of stachyose concentration. In soybean unique lines containing low raffinose or low stachyose were also found (Hitz et al 2002). The QTL analysis in soybean located four QTL for oligosaccharide content.…”
Section: Resultsmentioning
confidence: 94%
“…In the soybean genome appears one (out of two identified) raffinose synthase gene, completely associated with the low raffinose and low stachyose phenotype (Dierking & Bilyeu 2008). A single mutation in a soybean seed expressing the myo-inositol 1-phosphate synthase gene leads to a dramatic reduction of enzyme activity and decreases the accumulation of RFOs (Hitz et al 2002). The reduction of RFO level can be achieved also by genetic manipulation.…”
mentioning
confidence: 99%